Plant growth-promoting rhizobacteria effect on maize growth and microbial biomass in a chromium-contaminated soil - Silva, Raquel Sobral; Lopes Antunes, Jadson Emanuel; Aquino, Joao Pedro Alves de; Sousa, Ricardo Silva de; Melo, Wanderley Jose de [UNESP]; Ferreira Araujo, Ademir Sergio (Inst Agronomico, 2021)
Chromium contamination in soils affects plant growth and this metal can accumulate in plants tissues. In addition, Cr can affect soil microbial biomass and activity. On the other hand, plant growth-promoting rhizobacteria (PGPR) can protect plants against metals and, at the same time, promote plant growth and could alleviate adverse effects on microbial biomass. This study evaluated five PGPR on maize growth, Cr accumulation and soil microbial biomass in a Cr-contaminated soil. Five PGPR (LCC04, LCC41, LCC69, LCC81 and IPA403), isolated from soil under permanent application of composted tannery sludge and contaminated with Cr, were inoculated in maize plants grown in soils with (+Cr) and without (-Cr) Cr. In Cr-contaminated soil, LCC41 promoted the highest growth of maize, while LCC04 contributed with the highest N accumulation. The shoots of maize accumulated less Cr with LCC81, while LCC41 contributed to the highest Cr accumulation in roots. The translocation of Cr was highest with IPA403, while LCC81 contributed to reduce Cr translocation. In conclusion, LCC41 and LCC81 could be effective as PGPR inoculants to promote plant growth and reduce Cr accumulation in maize, respectively, in Cr contaminated soil.
Keywords: metals; tannery sludge; soil contamination; PGPR